2021
DOI: 10.1186/s12913-021-06614-x
|View full text |Cite
|
Sign up to set email alerts
|

“The system has to be health literate, too” - perspectives among healthcare professionals on health literacy in transcultural treatment settings

Abstract: Background Effective communication is a central aspect of organizational health literacy. Healthcare professionals are expected to ensure an effective and satisfactory flow of information and to support their patients in accessing, understanding, appraising, and applying health information. This qualitative study aimed to examine the health literacy-related challenges, needs, and applied solutions of healthcare professionals when engaging with persons with a migrant background. Based on the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 49 publications
0
29
0
1
Order By: Relevance
“…The selection of HWs as a target population allowed for accuracy of critical data reporting, as this group, by default, possesses adequate levels of health literacy, as well as scientific interest [69]. The vast proportion of young respondents participating in the study is deemed unique compared to similar surveys.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The selection of HWs as a target population allowed for accuracy of critical data reporting, as this group, by default, possesses adequate levels of health literacy, as well as scientific interest [69]. The vast proportion of young respondents participating in the study is deemed unique compared to similar surveys.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…This study is part of an overarching research project on ‘Gender-specific health literacy in individuals with migration background’ (GLIM). It includes two qualitative focus group studies, one on gender aspects of health literacy in migrants,41 and one on systemic aspects of intercultural treatment settings 42. Furthermore, a Cochrane review on interventions targeting the health literacy of migrants43 and a qualitative Cochrane review on gender differences in the health literacy of migrants44 are currently conducted within GLIM.…”
Section: Introductionmentioning
confidence: 99%
“…This was not something that the informants in the current study discussed outright, but they often returned to the importance of forming a common understanding of the context. Previous research has reported that healthcare personnel with a migration background have reported their background as an important factor that increased migrants' trust in them ( 34 ). Informants in the current study who shared cultural background or experience of migration with their participants described that they used this to level the playing field and approach the information within the CO together.…”
Section: Discussionmentioning
confidence: 99%